Aviation leadership : the accountable manager - Pierotti, Mark J. (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book identifies the responsibilities of management in the regulatory territories of the FAA (USA), the EASA (European Union) and the GCAA (UAE), identifying the daily challenges of leadership in ensuring their company is meeting the regulatory obligations of compliance, safety and security that will satisfy the regulator while also meeting the fiducial responsibilities of running an economically viable and efficient lean company that will satisfy the shareholders. Detailing each responsibility of the Accountable Manager, the author breaks them down to understandable and achievable elements where methods, systems and techniques can be applied to ensure the role holder is knowledgeable of accountabilities and is confident that they are not only compliant with the civil aviation regulations but also running an efficient and effective operation. This includes the defining of an Accountable Manager 'tool kit' as well as possible software 'dashboards' that focus the Accountable Manager on the important analytics such as the information and data available as well as making the maximum use of his expert Post Holder team. This book will be of interest to leadership of all aviation-related companies, such as airlines, charter operators, private and executive operators, flying schools, aircraft and component maintenance facilities, aircraft manufacturers, engine manufacturers, component manufacturers, regulators, law companies, leasing companies, banks and finance houses, departments of transport, etc; any relevant organization regulated and licensed by civil aviation authority. It can also be used by students within a wide range of aviation courses at colleges, universities, and training academies"--
OCLC-licensed vendor bibliographic record.
Keywords: Aircraft industry -- Management; TRANSPORTATION / Aviation / Commercial; BUSINESS & ECONOMICS / Industries / Transportation; TRANSPORTATION / Aviation / General